Deteksi Dini Kanker Payudara dan Lesi Prakanker Serviks pada Tenaga Kesehatan - Pringgowibowo, Jaeni; Suardi, Dodi; Anwar, Ruswana (Indonesian Journal of Obstetrics & Gynecology Science, 2023)
Tujuan: Kegiatan ini untuk menganalisis pengetahuan kanker payudara dan serviks tenaga kesehatan di faskes pertama kabupaten Bogor.Metode: Pelatihan deteksi dini kanker serviks dan payudara tenaga kesehatan di faskes pertama kabupaten Bogor dilakukan 6 hari melalui kuliah, dry lab, dan praktik lapangan. Dilakukan pre-test dan post-test untuk menilai pengetahuan tenaga kesehatan faskes pertama kabupaten Bogor.Hasil: Dari 75 responden perwakilan dari Puskesmas di kabupaten Bogor, 6,67% melakukan pelayanan deteksi dini kanker payudara dan 4,00% melakukan pelayanan deteksi dini kanker serviks. Pengetahuan responden setelah diklat, 100% responden menjawab benar tanda klinis IVA test negatif, pembacaan hasil IVA test setelah 1 menit, anjuran setelah krioterapi, tidak berhubungan selama 4 minggu setelah krioterapi, langkah pemeriksaan payudara, hal yang dilakukan bila menemukan kelainan pada payudara dan setelah digunakan, spekulum didekontaminasi 10 menit direndam dalam larutan klorin 0,5%. Pengetahuan meningkat signifikan mengenai perubahan leher rahim yang abnormal hampir selalu terjadi pada sambungan skuamo-kolumnar, yaitu naik 42,67% (56,00%pada menjadi 98,67% pada post-test).Kesimpulan: Terdapat peningkatan pengetahuan dan keterampilan setelah pelatihan kanker payudara dan serviks, terutama deteksi dini lesi prakanker serviks dan payudara, sehingga dapat disimpulkan upaya pelatihan penting untuk meningkatkan pengetahuan dan keterampilan deteksi dini kanker payudara dan serviks.Knowledge of Healthcare Providers on Early Detection of Breast Cancer and Precancerous Cervical LesionsAbstractObjective: This community service program aims to analyze the level of knowledge of breast cancer and cervical cancer by providing solutions through training for healthcare providers at primary health facilities in Bogor Regency.Method: Training on early detection of cervical cancer and breast cancer for doctors and midwives at primary health facilities at the Bogor Regency health office. The training was carried out for 6 days and was divided into lecture delivery, dry lab, and fieldwork practice at Padasuka Health Center and Puter Health Center. Pre-tests and post-tests were carried out to assess the level of knowledge of healthcare providers at primary health facilities in Bogor Regency.Results: Out of 75 representative respondents from each health center in Bogor Regency, 6.67% provided early detection of breast cancer, and 4.00% provided early detection of cervical cancer. As for respondents’ knowledge after being given training, as many as 100% of respondents answered correctly about the clinical signs of a negative VIA test reading the VIA test results after 1 minute, recommendations after cryotherapy, not to have sexual intercourse for 4 weeks after cryotherapy, steps for breast examination, what to do if they find abnormalities in the breast and after use, and the speculum that should be decontaminated for 10 minutes by immersion in 0.5% chlorine solution. Respondents’ knowledge significantly increased regarding abnormal cervical changes-dysplasia almost always occurred in the squamous columnar junction, which went up 42.67% (from 56.00% on the pre-test to 98.67% on the post-test).Conclusion: There was an increase in knowledge and skills after being given training on breast cancer and cervical cancer, especially knowledge about early detection of precancerous cervical lesions and breast cancer, so it can be concluded that training efforts are very important to increase knowledge and skills for early detection of breast cancer and cervical cancer.Key words: cervical cancer, breast cancer, VIA test